From Perceived Stress to Demoralization in Parkinson Disease: A Path Analysis - de Figueiredo, John M.; Zhu, Boheng; Patel, Amar; Kohn, Robert; Koo, Brian B.; Louis, Elan D. (Frontiers in Psychiatry, 2022)
Parkinson disease is associated with an increased risk of suicide that is not fully explained by higher rates of mental disorders. Demoralization in Parkinson disease is associated with a disruption in health-related quality of life and demoralized patients with Parkinson disease are more likely than controls to have suicidal ideation. Although demoralization is highly comorbid with depression and anxiety, it is unclear how they relate to each other. The objective of this study was to determine whether depression and anxiety are mediators between perceived stress and demoralization via a loss of the cognitive map manifesting as subjective incompetence. Ninety-five consecutive outpatients with Parkinson disease were evaluated for perceived stress, depression, anxiety, subjective incompetence, and demoralization using reliable and valid scales. Inclusion criteria were ages 40 to 90, intact cognition, and no current history of substance use. The setting was a Movement Disorders Clinic at a university-affiliated hospital. The outcome variable was demoralization, selected a priori. Mediators between perceived stress and demoralization were examined using path analysis. Depression, anxiety, and subjective incompetence were mediators between perceived stress and demoralization. Among all variables, subjective incompetence was the largest contributor to demoralization. Depression connected to demoralization indirectly via subjective incompetence, whereas anxiety bypassed subjective incompetence, connecting directly to demoralization. Early treatment and reversal of subjective incompetence and anxiety could potentially prevent the escalation of demoralization and the associated disruption in health-related quality of life and eventual suicide.